2022
DOI: 10.1101/2022.01.22.476743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The positive dimension of schizotypy is associated with a reduced attenuation and precision of self-generated touch

Abstract: The brain predicts the sensory consequences of our movements and uses these predictions to attenuate the perception of self-generated sensations. Accordingly, self-generated touch feels weaker than externally generated touch of identical intensity. In schizophrenia, this somatosensory attenuation is substantially reduced, suggesting that patients with positive symptoms fail to accurately predict and process self-generated touch. Here we hypothesized that a similar impairment might exist in healthy nonclinical … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 138 publications
(181 reference statements)
1
9
0
Order By: Relevance
“…Specifically, previous studies investigating interferences in the detection of a tactile stimulus by the concurrent somatosensory stimulation of another skin location (for a review, see Tamè et al., 2016 ) showed elevated thresholds for stimuli delivered within the same finger or hand ( Sherrick, 1964 ) and smaller effects, if present at all, for stimuli applied on different hands ( Gescheider et al., 1970 ; Laskin and Spencer, 1979 ). Crucially, any bimanual interferences disappear if the double touch stimuli are applied on homologous fingers (e.g., right and left index fingers) or if the two hands differ in their posture (e.g., one hand is palm up and the other is palm down) ( Tamè et al., 2011 ), which is precisely the hands’ configuration employed in the current attenuation and attenuation&gating conditions, and in all previous attenuation studies ( Asimakidou et al., 2022 ; Bays et al., 2006 ; Kilteni et al., 2018 , 2019 , 2020 , 2021 ; Kilteni and Ehrsson, 2017a , 2017b , 2020 ; Lalouni et al., 2020 ; Shergill et al., 2003 , 2005 , 2013 ), one should add. Therefore, bimanual tactile interferences are unlikely to explain somatosensory attenuation effects.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Specifically, previous studies investigating interferences in the detection of a tactile stimulus by the concurrent somatosensory stimulation of another skin location (for a review, see Tamè et al., 2016 ) showed elevated thresholds for stimuli delivered within the same finger or hand ( Sherrick, 1964 ) and smaller effects, if present at all, for stimuli applied on different hands ( Gescheider et al., 1970 ; Laskin and Spencer, 1979 ). Crucially, any bimanual interferences disappear if the double touch stimuli are applied on homologous fingers (e.g., right and left index fingers) or if the two hands differ in their posture (e.g., one hand is palm up and the other is palm down) ( Tamè et al., 2011 ), which is precisely the hands’ configuration employed in the current attenuation and attenuation&gating conditions, and in all previous attenuation studies ( Asimakidou et al., 2022 ; Bays et al., 2006 ; Kilteni et al., 2018 , 2019 , 2020 , 2021 ; Kilteni and Ehrsson, 2017a , 2017b , 2020 ; Lalouni et al., 2020 ; Shergill et al., 2003 , 2005 , 2013 ), one should add. Therefore, bimanual tactile interferences are unlikely to explain somatosensory attenuation effects.…”
Section: Discussionmentioning
confidence: 88%
“…Several experimental studies in humans have shown that the brain attenuates somatosensory reafference (i.e., all somatosensory inputs generated by one’s own movement, including inputs originating directly from the moving body part and inputs from other passive body parts being touched) compared with exafference. In behavioral research, this process refers to participants perceiving self-generated strokes, forces, or taps as weaker than external equivalents of the same intensity ( Asimakidou et al., 2022 ; Bays et al., 2005 , 2006 ; Blakemore et al., 1999b ; Kilteni et al., 2018 , 2019 , 2020 , 2021 ; Kilteni and Ehrsson, 2017a , 2017b ; Shergill et al., 2003 ; Walsh et al., 2011 ). This somatosensory attenuation is related to reduced activity in the secondary somatosensory cortex ( Blakemore et al., 1998 ; Kilteni and Ehrsson, 2020 ; Shergill et al., 2013 ) and the cerebellum ( Blakemore et al., 1998 , 2001 ; Kilteni and Ehrsson, 2020 ) and increased connectivity between the two areas ( Blakemore et al., 1999a ; Kilteni and Ehrsson, 2020 ) during self-generated touches compared with externally generated touches.…”
Section: Introductionmentioning
confidence: 99%
“…Clarifying how predictions about the sensory consequences of our movements affect our perception is fundamental to understanding the interaction between perception and action but also for clinical and neurobiological theories of psychosis spectrum disorders, such as schizophrenia (S.-J. ; P. R. and schizotypy (Asimakidou et al, 2022), as well as functional movement disorders ), Parkinson's disease and ageing . In the present study, two opposing hypotheses regarding how action influences somatosensory perception were contrasted: the attenuation model and the enhancement model.…”
Section: Discussionmentioning
confidence: 99%
“…In the somatosensory domain, evidence supporting the attenuation model has repeatedly shown that touch delivered to one (passive) hand by the other (active) hand (i.e., selfgenerated touch) is perceived as weaker or less ticklish (Asimakidou et al, 2022;; Sarah J. and evokes attenuated somatosensory cortical activation (Sarah J. compared to touch of identical intensity applied on the passive hand that is externally generated. In contrast, one study supporting the enhancement model has shown that the action of the active hand results in an increase in the perceived intensity of touch on the passive hand, provided that the active hand never receives touch simultaneously with the passive hand (i.e., hands do not make contact) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation